2013
DOI: 10.1111/1467-6427.12015
|View full text |Cite
|
Sign up to set email alerts
|

Revealing underlying vulnerable emotion in couple therapy: impact on session and final outcome

Abstract: This study examined how the revealing of underlying vulnerable emotion relates to session and final outcome in the context of emotion-focused therapy for couples. Segments of videotaped therapy sessions were rated on a measure of underlying vulnerable emotional expression for twentyfive couples. Results indicated that partners rated sessions in which underlying vulnerable emotion was expressed significantly more positively than control sessions on a measure of session outcome. Moreover, from pre to post, coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
(26 reference statements)
3
23
0
Order By: Relevance
“…This process can help them contain volatile emotions and learn to express and explore their issues in terms of primary emotions and core attachment needs. If clinicians can instead help clients higher in attachment anxiety express their issues in more contained ways by helping them look below the surface of secondary emotions and become aware of their primary emotions and attachment needs, their partners will likely see the person and their needs in new ways that help them soften as well as be more responsive (McKinnon and Greenberg, ). This will then, in turn, offer much needed reassurance to those higher in attachment anxiety that their needs can and will be met if they signal them more appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…This process can help them contain volatile emotions and learn to express and explore their issues in terms of primary emotions and core attachment needs. If clinicians can instead help clients higher in attachment anxiety express their issues in more contained ways by helping them look below the surface of secondary emotions and become aware of their primary emotions and attachment needs, their partners will likely see the person and their needs in new ways that help them soften as well as be more responsive (McKinnon and Greenberg, ). This will then, in turn, offer much needed reassurance to those higher in attachment anxiety that their needs can and will be met if they signal them more appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have provided indirect support for this assumption by demonstrating that closely related variables such as level of emotional experiencing and softening events are predictive of increased affiliative behavior and greater improvement from pre to post (e.g., Greenberg, Ford, Alden, & Johnson, ; Makinen & Johnson, ); however, none of these studies have focused specifically on vulnerability per se. To date, only one study has explicitly measured and linked vulnerable emotional expression to better outcomes in the context of EFCT (McKinnon & Greenberg, ). This study found that when partners’ ratings of sessions containing vulnerable emotional expression were compared to their ratings of control sessions, sessions containing vulnerable emotional expression were rated significantly more positively by both partners on a global measure of session outcome.…”
Section: Emotion Focused Couples Therapymentioning
confidence: 99%
“…A hallmark of the original model of emotionally focused couples' therapy (Greenberg & Johnson, ) was the strong emphasis on people expressing underlying vulnerable feelings to undo negative interactional cycles and the encouragement of the expression of adult unmet needs and responsiveness to these expressions. Support for this hypothesis has been demonstrated in a recent study (McKinnon, ; McKinnon & Greenberg, ) showing that the in‐session expression of vulnerable emotions predicts outcome. In our expansion of the original model, in EFT‐C, we also work toward self‐change and the resolution of pain stemming from unmet childhood needs that affect the couple interaction, in addition to working on interactional change.…”
mentioning
confidence: 84%